Integrasi Sosial Dalam Masyarakat Beragama Sebagai Mediasi Konflik Sosial - Sopiyan, Wawan; Hidayat, Rahmat Hidayat; Setiawati, Rini; Hadi, Fais Nurul (El-Ghiroh : Jurnal Studi Keislaman, 2022)
Relating to harmonization and social in the religious community will always get special attention. Especially if a change and progress is a common goal as a result of the hard work of people living side by side with one another. Aware of the appearance of a conflict and there will also be integration in the religious community which is likened to two sides of a coin. Where a conflict is a natural process in people's lives. But in these changes it is not particularly the conflict will be placed on the negative side always. This is why a religious social life fosters the integration and progress of a civilization of human life. And religious leaders are required to be able to maintain conflict in society in a positive and supportive direction. Then a social engineering related to integration is aimed at promoting peace and religious harmony. With great hope that this social integration process will be able to minimize the increase in issues of separatism, terrorism and religious radicalization that can damage religious harmony.